"This Is Not the Original Timeline": A Case Report of an Extended Dissociative Episode in a Healthy Young Male Accompanied with Severe Decline in Mental State. (3rd May 2021) - Tong, Godwin; Groom, Kieran; Ward, Louisa; Naeem, Muhammad
Abstract : Dissociation is a disconnection between a person's thoughts, memories, feelings, actions, or sense of who he or she is. Dissociative disorders can be described and understood using the combination of five core symptoms: amnesia, depersonalisation, derealisation, identity confusion, or identity alteration. They are frequently associated with previous experience of trauma. The challenge in diagnosis and the lifetime prevalence of approximately 10% in the general population and clinical psychiatric setting ensures the relevance of this case. We write about a 21-year-old gentleman with history of autism and obsessive compulsive disorder, but no significant medical history was presented to the emergency department with increased anxiety, subsequently progressing to agitation, pacing, and becoming nonverbal. No significant findings were uncovered on laboratory blood testing (other than prolactin 737 mu/L and phosphate 0.35 mmol/L), lumbar puncture, or brain imaging. Consequently, he was admitted to a psychiatric unit for assessment. The patient continued to present with severe disorientation, limited speech, and altered state of consciousness with occasional spastic-like movements. Antipsychotic and benzodiazepine medication was initiated, with no significant change in presentation. The patient continued to be witnessed wandering and having incoherent speech. First signs of improvement came 21 days postadmission with brief conversation and lucidity. This continued to improve over the next 7 days where he was reported to be at his baseline mental state. Environmental stressors including university examinations, the COVID-19 pandemic, and recent contact with his estranged father were possible precipitants to the episode. The patient reported almost complete unawareness of the psychiatric admission. A diagnosis of dissociative disorder, unspecified, was given. This case shows the management and diagnostic challenges of patients presenting with the aforementioned symptoms. There are no formal guidelines for the management of treating dissociative episodes, and this case report suggests the possible benefits of a drug-free period of watchful waiting upon admission.